Hospital Financial Strategy in Response to COVID-19: A Systematic Review - Yulius, Suci Kirana; Soewondo, Prastuti; Carolinsia, Brenda (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: The COVID-19 pandemic had resulted in an unprecedented strain on healthcare systems. Hospitals are faced with the unexpected influx of patients, increasing need for protection equipment and infection control procedures, increased workload and operational hours, and the depleting revenues due to closure of elective services. This study aims to further analyze the financial strategies used by hospitals to ensure its operations and to overcome financial challenges presented by the COVID-19 pandemic.Subjects and Method: A systematic review has been identified using four databases: MEDLINE (PubMed), Google Scholar, SCOPUS, and MedSci. This search in literature was published articles from January 2020 to June 2021 using PRISMA guidelines. The keywords used “COVID-19” OR “SARS-CoV-2” AND (ii)